Un’austera Venezia di fine XVIII secolo - Baldan, Andrea (Quaderni Veneti, 2018)
The poem La Cuccagna by Giuseppe Lazzari was published during the Venetian Revolution of 1797. This paper will provide an edition based on its two extant copies as well as a commentary, whose aim is to contextualize the poem in regards to the historic events after the fall of the Republic of Venice. Inscribed in the long literary tradition of the ‘land of Cockayne’ or ‘feast of Cockayne’, the text exhibits nonetheless a significant deviation from its more traditional expressions. Taking advantage of the cuccagna’s meaning of wealth and freedom, the author praises Napoleon and the  revolution, having faith in new social and political circumstances, while at the same time claiming for radical reforms.